Techniques for Extraction of Brewer’s Spent Grain Polyphenols: a Review - Guido, Luis F. (2019)
Million tons of brewer’s spent grain (BSG) are annually produced worldwide as brewing industry by-products. BSG represents a valuable source of phenolic compounds, which have attracted much attention due to their diverse health benefits. Relevant strategies have been developed for their efficient extraction, in order to commercially exploit these resources. This review focuses on the current extraction methods used to obtain phenolic compounds from BSG, ranging from more traditional to advanced techniques. The commonly used methods are the conventional solid–liquid extractions, employing organic solvents, alkaline, and enzymatic reactions. However, the inherent difficulties in screening and obtaining these compounds have led to the development of advanced extraction techniques. Pressurized fluid extraction, supercritical extractions, and microwave-assisted and ultrasound-assisted extractions are some of the novel extraction techniques that have been recently explored. These techniques have been mostly applied for phenolic recovery from barley and malt, as well as other types of cereals. In this review, it is shown that these novel techniques may provide an innovative approach to extract phenolics from BSG or related products, following an in-depth discussion on the major strengths and weaknesses identified in each technique.